Cancer metabolism and mitochondria: Finding novel mechanisms to fight tumours - Sonia Missiroli; Mariasole Perrone; Ilaria Genovese; Paolo Pinton; Carlotta Giorgi (EBioMedicine, 2020)
Mitochondria are dynamic organelles that have essential metabolic activity and are regarded as signalling hubs with biosynthetic, bioenergetics and signalling functions that orchestrate key biological pathways. However, mitochondria can influence all processes linked to oncogenesis, starting from malignant transformation to metastatic dissemination. In this review, we describe how alterations in the mitochondrial metabolic status contribute to the acquisition of typical malignant traits, discussing the most recent discoveries and the many unanswered questions. We also highlight that expanding our understanding of mitochondrial regulation and function mechanisms in the context of cancer cell metabolism could be an important task in biomedical research, thus offering the possibility of targeting mitochondria for the treatment of cancer.